Genome-wide identification, isolation and expression analysis of auxin response factor (ARF) gene family in sweet orange (Citrus sinensis) - Li, Si-Bei; OuYang, Wei-Zhi; Hou, Xiao-Jin; Xie, Liang-Liang; Hu, Chun-Gen; Zhang, Jin-Zhi (Frontiers in Plant Science, 2015)
Auxin response factors (ARFs) are an important family of proteins in auxin-mediated response, with key roles in various physiological and biochemical processes. To date, a genome-wide overview of the ARF gene family in citrus was not available. A systematic analysis of this gene family in citrus was begun by carrying out a genome-wide search for the homologues of auxin response genes. A total of 19 non-redundant ARF genes (CiARF) were identified and validated from the sweet orange genome. A comprehensive overview of the CiARF gene family was undertaken, including the gene structures, phylogeny, chromosome locations, conserved motifs, and cis-elements in promoter sequences. Furthermore, expression profiling using real-time PCR revealed many CiARF genes, albeit with different patterns depending on types of tissues and/or developmental stages. Comprehensive expression analysis of these genes was also performed under two hormone treatments using real-time PCR. Indole-3-acetic acid and N-1-napthylphthalamic acid treatment experiments revealed differential up-regulation and down-regulation, respectively, of the 19 citrus ARF genes in the callus of sweet orange. Our comprehensive analysis of ARF genes further elucidates the roles of CiARF family members in citrus growth and development.